TINJAUAN YURIDIS DUALISME STATUS HUKUM INDIVIDU PENJABAT DIREKTUR KORPORASI - Handoyo Prasetyo; Subakdi Subakdi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
The corporation is one of the backbones of economic growth in Indonesia. The corporation as a legal subject in the form of a legal entity due to its functional nature, will always be represented by an individual who is authorized by law to carry out corporate management functions. Individual Director of a corporation who comes from an internal corporation raises a dualism of legal status that covers Individual of Director, namely the Manpower Law and the Limited Liability Company Law. In addition, Individual of Director must also comply with all regulations related to their business activities (compliance principles). This research is made by looking at the factors that cause the dualism of legal status of Individual Director and the efforts made to provide legal protection for employees who act as corporate director in applying the principle of compliance to ensure the achievement of good corporate governance. Because this research is a research in the field of law, this research uses a normative juridical research method which is descriptive analytical in nature, to analyze the phenomena and what factors cause these problems / phenomena, namely the dualism status of Individual Director law. From this research, it was found that the factors of the dualism of legal status of Individual Director were because the holding company did not give up the employment status of individual employees who were appointed as directors and in contrast, Individual of Director were also reluctant to give up their employment relationship with the holding company. In order to protect the Individual Director from all legal risks that he faces in the implementation of the functions of the board of directors, the principle of compliance must be implemented properly and always act in a professional manner for the advancement of the corporation. Korporasi menjadi salah satu tulang punggung pertumbuhan ekonomi di Indonesia. Korporasi sebagai subjek hukum yang berbentuk badan hukum (rechtspersoon) karena sifat fungsionalnya, akan selalu diwakili oleh seorang individu yang diberikan kewenangan oleh undang-undang untuk melaksanakan fungsi kepengurusan korporasi. Individu Direktur korporasi yang berasal dari karyawan internal korporasi menimbulkan dualisme status hukum yang menaungi Individu Direktur yakni Undang-undang Ketenagakerjaan dan Undang-undang Perseroan Terbatas. Disamping itu Individu Direktur juga harus mentaati semua peraturan yang terkait dengan kegiatan usahanya (compliance principle). Penelitian ini dibuat dengan tujuan mengetahui faktor-faktor yang menjadi penyebab terjadinya dualisme status hukum Individu Direktur korporasi dan upaya yang dilakukan guna memberikan perlindungan hukum bagi karyawan yang menjabat sebagai direktur korporasi dalam menerapkan compliance principle guna memastikan tercapainya tata kelola perusahaan yang baik (good corporate governance). Karena penelitian ini adalah penelitian di bidang hukum, maka penelitian ini mempergunakan metode penelitian yuridis normatif yang bersifat deskriptif analitis, untuk menganalisis fenomena yang ditemukan dan faktor apa yang menyebabkan timbulnya masalah / fenomena tersebut yakni adanya dualisme status hukum Individu Direktur. Dari penelitian ini ditemukan faktor-faktor timbulnya dualisme sistem hukum yang menaungi Individu Direktur di disebabkan karena korporasi induk (holding company) tidak melepaskan status ketenagakerjaan individu karyawan yang diangkat menjadi direktur dan sebalinya Individu Direktur juga enggan melepaskan hubungan ketenagakerjaannya dengan holding company. Untuk melindungi Individu Direktur dari segala resiko hukum yang dihadapinya dalam pelaksanaan fungsi direksi, maka compliance principle harus dilaksanakan secara baik dan senantiasa bertindak secara profesional demi kemajuan korporasi.